A Study of Some Results of Inverse Dominations on Graph: Exploring Inverse Dominations and Graph Relationships (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The upper and lower limits show the absolute superiority of the direct product of the graphs. The boundaries include the total number of {2}, the total number of 2 times for domination and the number of factors for open packaging. The total number of such relationships is accurate. A series of diagrams shows the best possible limits. The numbers of products that dominate direct graphics. We show that the step domination number of any tree T satisfies. where n is the number of vertices of T, an d D is its diameter. It is also proved that if some requirements are set ona tree T then,